Glyphosate degradation in Malaysian sandy loam soil amended with cow dung or rice husk ash as influenced by soil moisture content - Garba, Jamilu; Samsuri, Abd Wahid; Ahmad Hamdani, Muhammad Saiful; Sadiq, Tariq Faruq; Nabayi, Abba (Malaysian Society of Soil Science, 2022)
This study investigated the effect of cow dung or rice husk ash amendment on glyphosate degradation in a Malaysian sandy loam soil under three moisture regimes. The control and soils amended with 10 tons ha-1 of either cow dung or rice husk ash were spiked with 5000 μg g-1 of glyphosate. Water was added accordingly to obtain soil moisture content equivalent to either a submerged condition, field capacity or permanent wilting point. Glyphosate degradation was monitored for 65 days and the data obtained was fitted to first order-double exponential decay model (FODED). The results revealed that glyphosate degradation occurred in two-phases; an initial high degradation rate followed by a slow rate representing degradation of labile and non-labile phases, respectively. The rate constants of the labile phases ranged from 0.0063 to 0.0604 μg day-1 while those of non-labile phases were from 0.0077 to 0.0732 μg day-1. The degradation rate was generally higher in the labile phase. Irrespective of moisture content, the degradation data from the cow dung-amended soil fitted the FODED model best (0.042 ≥ r2 ≤ 0.909) followed by the rice husk ash-amended soil (0.023 ≥ r2 ≤ 0.914) and the control (0.030 ≥ r2 ≤ 0.756). Meanwhile, irrespective of the amendments, soils maintained at field capacity had the highest degradation rate in labile phases (k1 = 0.0371 – 0.0604 μg day-1) while at non-labile phases, soils maintained at permanent wilting point recorded the highest rate (k2 = 0.0077 – 0.0732 μg day-1). The soils maintained at field capacity generally had the lowest glyphosate half-life (11- 42 days) followed by soils at permanent wilting point (9 – 110 days), with the longest half-life being shown by the submerged soils (13-178 days). It can be concluded that the application of cow dung or rice husk ash increased glyphosate degradation in the soil especially when the soil moisture content was maintained at field capacity.